Halal Tourism: Potential and Prospects in Improving the Economy and Developing Mosque-Based Regional Tourism (Case Study of Nur Ala Nur Gread Mosque, Mandailing Natal) - Lubis, Delima Sari; Rahmat, Paisal; Nisa Brt, Ainun; Aulia, Nurhikmah (Wealth: Journal of Islamic Banking and Finance, 2023)
This study discusses about Halal Tourism: Potential and Prospects in Improving the Economy and Developing Regional Tourism (Case Study of the Great Mosque of Nur Ala Nur Mandailing Natal), because the potential of halal tourism in Mandailing Natal supported by the majority Muslim population, has the Oldest Boarding School in Sumatra (Mustafawiyah) and having the most Islamic boarding schools in cities at North Sumatra is expected to have an influence on improving the economy and developing regional tourism as a mosque-based halal tourist destination. The research was conducted with qualitative analysis to identify the potential of Mandailing Natal Regency as a mosque-based halal tourism destination in North Sumatra Province. The results of this study. First, that the Mandailing Natal District has the potential to increase the economy and develop tourism Mosque-based areas because they are supported by the social culture of the majority Muslim community, also supported by the number of tourist data that increases every year, as well as the most Islamic boarding schools in North Sumatra Province and the oldest in Sumatra. Second, the potential for halal tourism of the Great Mosque of Nur Ala Nur Mandailing Natal has progressed every year because it is supported by the 20 shops and 1 Caffe Mandhahiling Coffee and Mobile Trade in the mosque area, also near to Aek Batang Gadis tourism, Panatapan, Raja Batu Park, and Sampuraga